2003
DOI: 10.1097/00006454-200301000-00012
|View full text |Cite
|
Sign up to set email alerts
|

A wider role for congenital cytomegalovirus infection in sensorineural hearing loss

Abstract: The results suggest that congenital CMV infection has a more relevant role in the etiology of SNHL than previously reported. The data obtained in both groups suggest that 20 to 30% of all deafness cases are caused by CMV. The percent of congenital CMV cases alone appears to account for all the cases previously attributed to all congenital infections. More than 40% of deafness cases with an unknown cause, needing rehabilitation, are caused by congenital CMV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
1
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(125 citation statements)
references
References 11 publications
5
109
1
9
Order By: Relevance
“…In 13 children with sensorineural hearing loss (54% of the study group), the etiology remains undetermined. A recent Italian study, utilizing PCR analysis of newborn spots for CMV DNA, suggests that intrauterine CMV infection accounts for as many as 30% of children with sensorineural hearing loss [Barbi et al, 2003]. In an effort to thoroughly examine this population for all components of hearing loss, we are collaborating on a CDC-funded study of CMV infection to determine its contribution to newborn hearing loss in Utah.…”
Section: Discussionmentioning
confidence: 99%
“…In 13 children with sensorineural hearing loss (54% of the study group), the etiology remains undetermined. A recent Italian study, utilizing PCR analysis of newborn spots for CMV DNA, suggests that intrauterine CMV infection accounts for as many as 30% of children with sensorineural hearing loss [Barbi et al, 2003]. In an effort to thoroughly examine this population for all components of hearing loss, we are collaborating on a CDC-funded study of CMV infection to determine its contribution to newborn hearing loss in Utah.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45] However, it is assumed that the importance of asymptomatic cCMV as a cause of hearing loss may be higher than currently believed. 3,46,47 This systematic review provides an overview of the prevalence of cCMV-related hearing loss based on the literature of the past 50 years and aims at better defining the nature of cCMV-associated hearing loss and the importance of cCMV among patients with childhood hearing loss.…”
mentioning
confidence: 99%
“…This test has also been used to evaluate the prevalence of congenital CMV infection in children with cortical development disorders (such as pachigiria and leucodystrophy of unknown origin) (52). The same test revealed that 20-30% of all cases of infantile deafness were due to congenital CMV infection (53,54).…”
Section: (Asd) Are Neurodevelopmental Disorders Without a Definitive mentioning
confidence: 99%